Clinical, cytogenetic and molecular analysis of three 46,XX males - Plöchl, Engelbert; Vlasak, I.; Rittinger, O.; Bergendi, E.; Stopar, M.; Kurnik, P.; Nachtigall-Papadopoulos, Nikolaos; Zierler, H.; Rappold, Gudrun; Schiebel, Katrin (The journal of pediatric endocrinology and metabolism, 1999)
Der Artikel Clinical, Cytogenetic and Molecular Analysis of Three 46,XX Males wurde am 1. Mai 1999 in der Zeitschrift Journal of Pediatric Endocrinology and Metabolism (Band 12, Heft 3) veröffentlicht.
Gesehen am 07.04.2021